Islamic Education-Based Parenting in Developing Religious Attitudes of Children in Orphanages - Nur Saadah Fitriah; Makhmud Syafe’i; Nurti Budianti; Chanda Chansa Thelma (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Islamic Education Based Parenting in Developing Religious Attitudes of Children in OrphanagesObjective: This study aims to analyze the Islamic education model based on parenting styles applied at Al-Kautsar Lembang Orphanage in developing religious attitudes in children. Methods: This study used a mixed-method approach. The research subjects were children aged 10 to 14 years. Data were collected through participatory observation, in-depth interviews, religious attitude scales, and documentation. Descriptive statistical analysis was used to interpret the data. Results: The parenting-based Islamic education model implemented at Al-Kautsar Orphanage significantly contributes in developing children's religious character and attitudes. Conclusion: To effectively foster children's religious character and attitudes through parenting-based Islamic education, specific strategies are required to ensure that all children receive individualized attention tailored to their needs. Contribution: This study serves as a guide for orphanage caregivers in applying effective approaches to nurture religious values in children.INDONESIAN: Pola Asuh berbasis Pendidikan Islam dalam Membangun Sikap Keagamaan Anak di Panti AsuhanTujuan: Penelitian ini bertujuan untuk menganalisis model pendidikan Islam berbasis pola asuh yang diterapkan di Panti Asuhan Al-Kautsar Lembang dalam membentuk sikap religius pada anak. Metode: Penelitian ini menggunakan pendekatan metode campuran. Subjek penelitian adalah anak-anak berusia 10 hingga 14 tahun. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, skala sikap religius, dan dokumentasi. Analisis statistik deskriptif digunakan untuk menginterpretasikan data. Hasil: Model pendidikan Islam berbasis pola asuh yang diterapkan di Panti Asuhan Al-Kautsar memberikan dampak yang signifikan dalam membentuk karakter dan sikap religius anak. Kesimpulan: Untuk membentuk karakter dan sikap religius anak secara efektif melalui pendidikan islam berbasis pola asuh, diperlukan strategi khusus untuk memastikan bahwa semua anak menerima perhatian yang disesuaikan dengan kebutuhan masing-masing. Kontribusi: Penelitian ini memberikan panduan bagi para pengasuh di panti asuhan tentang pendekatan terbaik untuk mengembangkan nilai-nilai agama anak